Isotopic and Petrologic Investigation, and a Thermomechanical Model of Genesis of Large-Volume Rhyolites in Arc Environments: Karymshina Volcanic Complex, Kamchatka, Russia - Bindeman, Ilya N.; Leonov, Vladimir L.; Colón, Dylan P.; Rogozin, Aleksey N.; Shipley, Niccole; Jicha, Brian; Loewen, Matthew W.; Gerya, Taras V. (Frontiers in Earth Science, 2019)
This study examines the largest center of silicic magmatism, 4-0.5 Ma Karymshina Volcanic Complex, which also includes the largest 25x15 km Karymshina caldera in Kamchatka. A series of rhyolitic tuff eruptions at 4Ma were followed by the main eruption at 1.78Ma produced an estimated 800 km3 of rhyolitic ignimbrites followed by ring-tracture high-silica rhyolitic post-caldera extrusions. We here present results a of geologic, petrologic, and isotopic study of this complex, and present new Ar-Ar ages, and isotopic values of rocks. Basement of the complex is formed by 4-3.5 Ma rhyolitic ruffs, the oldest pre-1.78Ma caldera ignimbrites and intrusions include a diversity of compositions from basalts to rhyolites. All rocks are crystal-rich with quartz, plagioclase, biotite, and amphibole phenocrysts. Temporal trends in δ18O, 87Sr/86Sr, 144Nd/143Nd indicate values comparable to neighboring volcanoes, increase in homogeneity, and temporal increase in mantle-derived Sr and Nd with increasing differentiation over the last 4 million years. Data are consistent with a batholithic scale magma chamber formed by primarily fractional crystallization of mantle derived composition and assimilation of Cretaceous and younger crust, driven by basaltic volcanism and mantle delaminations. Rhyolite-MELTS crystallization models favor shallow (2 kbar) differentiation conditions and varying quantities of assimilated amphibolite partial melt and hydrothermally-altered silicic rock to reproduce the compositions seen at Karymshina Eruptive Center. Results of thermomechanical modeling with a typical 0.001km3/yr eruption rate of hydrous basalt into a Kamchatkan arc crust produces two magma bodies, one near the Moho and the other engulfing the entire section of upper crust. Basalt is getting trapped in the lower portion of the upper crustal magma body, which exists as partially molten to solid state. Differentiation products of basalt periodically mix with the resident magma diluting its crustal isotopic signatures. At the end of the magmatism crust is getting thicker by 8 km. Modeling show that the only way to generate large spikes of rhyolitic magmatism is through delamination of cumulates in the lower crust. The paper also present chemical dataset for Pacific ashes from ODDP 882 and 883 and compares them to Karymshina ignimbrites and two other other Pleistocene calderas studied by us earlier.